2006
DOI: 10.1007/s10479-006-7380-3
|View full text |Cite
|
Sign up to set email alerts
|

A model for standardizing human decisions concerning service-contracts management

Abstract: Increased expectations of today's customers are causing businesses to offer a variety of warranty contracts for their products. Because of the intense customer contact that takes place during the process of supporting a contract, the planning for contracts has to not only contend with the unpredictable and low demands of the service parts, but must also rely on human decision-making concerning a number of subjective factors. These subjective factors, which are related to the customer, the contract and the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For instance, AHP has emerged as a popular and practical tool for decision making, but it suffers from consistency problems (Wang and Chang, 2007). Sundarraj (2006) suggests that because decision makers specifying preferences in distributed locations will make incorrect decisions when utilizing the AHP approach, many organizations' applications of the AHP approach vary significantly. Tavana et al (2010) noted that there has been criticism of AHP in the operations research literature, including preference reversals, because of the questionable theoretical basis.…”
Section: Fuzzy Preference Relations (Fpr)mentioning
confidence: 99%
“…For instance, AHP has emerged as a popular and practical tool for decision making, but it suffers from consistency problems (Wang and Chang, 2007). Sundarraj (2006) suggests that because decision makers specifying preferences in distributed locations will make incorrect decisions when utilizing the AHP approach, many organizations' applications of the AHP approach vary significantly. Tavana et al (2010) noted that there has been criticism of AHP in the operations research literature, including preference reversals, because of the questionable theoretical basis.…”
Section: Fuzzy Preference Relations (Fpr)mentioning
confidence: 99%
“…For instance, AHP has emerged as a popular and practical tool for decision-making, but it still suffers from consistency problems (Wang and Chen 2007). Sundarraj (2006) discussed that because of decision-makers specifying the preferences in distributed locations will make wrong decision when utilizing AHP approach, many organizations tend to apply AHP approach vary considerably. Moreover, Tavana et al (2010) concluded that there has been some criticism of the AHP in the operations research literature including preference reversals because of questioned the theoretical basis, and therefore, they proposed a new multi-criteria decision analysis model to avoid the controversies associated with rank reversal.…”
Section: Consistent Fuzzy Preference Relationsmentioning
confidence: 99%
“…Yao and Liu (2005) studied competitive pricing of mixed retail and e-tail distribution channels for the Bertrand and the Stackelberg models, they proposed an appropriate strategy for the decision maker to adopt when adding an e-tail channel. Sundarraj (2006) focused on offering a variety of warranty contracts to investigate customer's strategy.…”
Section: Literature Reviewmentioning
confidence: 99%